Late and Instable Sleep Phasing is Associated With Irregular Eating Patterns in Eating Disorders. Issue 9 (25th March 2020) - Linnaranta, Outi; Bourguignon, Clément; Crescenzi, Olivia; Sibthorpe, Duncan; Buyukkurt, Asli; Steiger, Howard; Storch, Kai-Florian
Abstract: Background: Sleep problems are common in eating disorders (EDs). Purpose: We evaluated whether sleep-phasing regularity associates with the regularity of daily eating events. Methods: ED patients ( n = 29) completed hourly charts of mood and eating occasions for 2 weeks. Locomotor activity was recorded continuously by wrist actigraphy for a minimum of 10 days, and sleep was calculated based on periods of inactivity. We computed the center of daily inactivity (CenDI) as a measure of sleep phasing and consolidation of the daily inactivity (ConDI) as a measure of daily sleep rhythm strength. We assessed interday irregularities in the temporal structure of food intake using the standard deviation ( SD ) of frequency (I FRQ ), timing (I TIM ), and interval (I INT ) of food intake. A self-evaluation of other characteristics included mood, anxiety, and early trauma. Results: A later phasing of sleep associated with a lower frequency of eating (eating frequency with the CenDI rho = −0.49, p = .007). The phasing and rhythmic strength of sleep correlated with the degree of eating irregularity (CenDI with I TIM rho = 0.48, p = .008 and with I INT rho = 0.56, p = .002; SD of CenDI with I TIM rho = 0.47, p = .010, and SD of ConDI with I INT rho = 0.37, p = .048). Childhood Trauma Questionnaire showed associations with variation of sleep onset (rho = −0.51, p = .005) and with I FRQ (rho = 0.43, p = .023). Conclusions: Late and variable phasing of sleep associated robustly with irregular pattern of eating. Larger data sets are warranted to enable the analysis of diagnostic subgroups, current medication, and current symptomatology and to confirm the likely bidirectional association between eating pattern stability and the timing of sleep. Abstract : In eating disorders, timing of sleep was late and irregular. Later sleep associated with a lower frequency and later and variable sleep with more irregular eating.